2019
DOI: 10.1002/ptr.6593
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV reverses simvastatin‐induced skeletal muscle injury by activating the AMPK‐PGC‐1α signalling pathway

Abstract: In this study, we investigated the effect of astragaloside IV on skeletal muscle energy metabolism disorder caused by statins and explored the possible mechanisms. Highfat diet-fed apolipoprotein E knockout (ApoE −/− ) mice performed aerobic exercise and were administered simvastatin, simvastatin + trimetazidine, or simvastatin + astragaloside IV by gavage. At the end of treatment, exercise performance was assessed by the hanging grid test, forelimb grip test, and running tolerance test.Moreover, plasma lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…What is more, the AS-IV was systemic administrated by gavage in this study; its biofunction on the central nervous system cannot be ignored and should be studied in the future via patch clamp-based methods. Through targeting multiple genes and downstream pathways such as AMPK [29], Hif-1α [30], and TLR4 [31], AS-IV demonstrated potential cardio-protective and immunological enhancement activities through experimentation in vitro and in vivo [32]. In this research, pBOO suppressed the AMPK-Ulk1 signaling, while AS-IV treatment reversed this effect.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…What is more, the AS-IV was systemic administrated by gavage in this study; its biofunction on the central nervous system cannot be ignored and should be studied in the future via patch clamp-based methods. Through targeting multiple genes and downstream pathways such as AMPK [29], Hif-1α [30], and TLR4 [31], AS-IV demonstrated potential cardio-protective and immunological enhancement activities through experimentation in vitro and in vivo [32]. In this research, pBOO suppressed the AMPK-Ulk1 signaling, while AS-IV treatment reversed this effect.…”
Section: Discussionmentioning
confidence: 66%
“…Through targeting multiple genes and downstream pathways such as AMPK [ 29 ], Hif-1 α [ 30 ], and TLR4 [ 31 ], AS-IV demonstrated potential cardio-protective and immunological enhancement activities through experimentation in vitro and in vivo [ 32 ]. In this research, pBOO suppressed the AMPK-Ulk1 signaling, while AS-IV treatment reversed this effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the data have been obtained in cells, rats and mice, as there have been few clinical trials on the effect of astragaloside IV in stroke patients. We searched for articles on clinical trials of astragaloside IV and found that astragaloside IV has ameliorative effects on skeletal muscle injury ( Jiang et al, 2020 ), precancerous lesions of gastric carcinoma ( Zhang et al, 2018 ), liver fibrosis ( Wang et al, 2021 ), induction of natriuresis ( Ai et al, 2008 ), and heart failure ( Luo et al, 1995 ). However, there are very few clinical publication on the protective effect of astragaloside IV on the brain.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…Astragaloside IV, a saponin puri ed from Astragalus, has been widely used for a long time in traditional Chinese medicine to treat ischemic diseases. Numerous studies have shown that Astragalus has positive effects, such as protecting hypoxic myocardial cells [12], promoting angiogenesis [13], inhibiting muscle damage [14]. The potential mechanisms include activation of the PI3K/Akt signaling pathway, JAK2/STAT3 and ERK1/2 signaling pathways [15], AMPK signaling pathway [16] and overexpression of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1a (HIF-1a) [17].…”
Section: Introductionmentioning
confidence: 99%